Utilization of the Book Hadīṡ Kulla Yaum in Arabic Conversation Habituation at Al-Lathifiyah Boarding School - Fahma, Zidnia; Maghfurin, Ahmad; Asy'ari, Hasyim (Study Program of Arabic Language Teaching, 2026)
This study aims to examine the utilization of the book Hadīṡ Kulla Yaum in the Arabic conversation habituation program and its contribution to the development of students’ speaking skills. The research employed a qualitative, descriptive case study design to obtain an in-depth understanding of the implementation of Arabic conversation habituation in the Islamic boarding school environment. This study was conducted at Al-Lathifiyah Islamic Boarding School, located in Brati District, Grobogan Regency, Central Java, Indonesia. The data were collected through observation, interviews, and documentation involving the head of the boarding school, Arabic teachers, conversation supervisors, and students participating in the Arabic habituation program. The data were analyzed using the interactive analysis model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the utilization of the book Hadīṡ Kulla Yaum contributes significantly to the improvement of students’ Arabic speaking skills through several habituation strategies, including routine conversation practice, repetitive vocabulary pronunciation exercises, contextual vocabulary use, sentence construction practice, spontaneous communication, two-way interaction, the creation of a supportive language environment, and scheduled Arabic language use. The results indicate improvements in speaking fluency, pronunciation accuracy, vocabulary mastery, confidence, spontaneous responses, and consistency in using Arabic in daily communication. Furthermore, the study found that the program's success is strongly supported by the boarding school's communicative environment, which encourages students to practice Arabic in real-life interactions actively. Therefore, the utilization of Hadīṡ Kulla Yaum through communicative habituation can be considered an effective approach to supporting the development of Arabic-speaking skills in Islamic boarding school settings.